The alikayasi canyon-channel system (Miocene, Southeast Turkey) compared with the south brae fan system (Upper Jurassic, North Sea); Characterizing sand and gravel-filled channel complexes in coarse-grained deep-water systems without gravel cone geometries - Jimenez, Ramon Lopez; Cronin, Bryan T.; Çelik, Hasan; Turner, Colin C.; Bastidas, Rodrigo E.; Kneller, Benjamin C. (American Association of Petroleum Geologists, 2018)
The Alikayasi canyon-channel system of the Miocene Maras Basin, eastern Turkey, is compared with the South Brae fan, South Viking Graben, United Kingdom sector, North Sea, demonstrating the importance of outcrop analogs to subsurface oil reservoirs. The Alikayasi canyon-channel is a coarse-grained, deep-water slope depositional system that developed in a contractional tectonic setting south of a large continental landmass. Sediment was fed through large, stable river systems and fan deltas, across a relatively narrow continental shelf, through gullies directly into the head of the slope system. Coarse sediment supply at Alikayasi was continuous, but periodic increases in tectonism caused increases in depositional slope, and hence canyon-cutting. First-order erosional surfaces mark such pulsed reactivation of the canyon-channel complex system. During slope steepening, canyon reincision took place, with sediment bypass downdip to the south. Backfilling of the canyon-channel complex system, alternating with pulses of sediment bypass, occurred during periods of more stable tectonic conditions, where the development of channel-overbank systems with aggradational channel levee elements is recognized. The South Brae fan is a coarse-grained, channelized lower base-of-slope system that developed in an extensional setting outboard of a relatively small landmass to the west and northwest. In the earlier, most active phase of rifting, high relief developed on the footwall and supply of coarse sediment was more or less continuous to the graben-margin trough, resulting in thick conglomeratic sections that lie beneath the South Brae reservoir. In later phases, as the graben-margin trough filled and the relief on the footwall decreased, deposition of gravels and sands in channels was more pronounced, muds were deposited close to channel systems, and sand deposition extended into the basin. Periodic interruptions in coarse sediment supply for substantial time periods led to deposition of field-wide muds. Coarse sediment supply then resumed, probably as a result of renewed tectonic activity that uplifted the footwall, initially resulting in down-cutting into the field-wide mudstone and bypass of sand into the basin. This was followed by backfilling of developing channels with gravel and sand and the development of interchannel muddy levees. Despite some differences in scale, channel systems at South Brae resemble canyon and channel complex systems like the Turkish Maras Basin examples. South Brae channel bases are erosional, at least in the thalwegs, as are the bases of Alikayasi channel complexes. Channel to channel-margin facies sequences at South Brae resemble to some extent channel fill- overbank sequences at Alikayasi. This is the main area where more detailed study of the geometric relationships between exposed channel fills and overbank deposits at Alikayasi might lead to revised interpretation of depositionally related units at South Brae, and hence aid more accurate reservoir mapping. © 2018 by The American Association of Petroleum Geologists.
Keywords: Atlantic Ocean; North Sea; Viking Graben; canyon; deep water; depositional environment; fan delta; geometry; gravel; Jurassic; Miocene; oil field; sand and gravel